Measurement of the mass and lifetime of the [Omega]-b baryon - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review, 2016)
A proton-proton collision data sample, corresponding to an integrated luminosity of 3 fb−1 collected by LHCb at √s=7 and 8 TeV, is used to reconstruct 63±9 Ω−b→Ω0cπ−, Ω0c→pK−K−π+ decays. Using the Ξ−b→Ξ0cπ−, Ξ0c→pK−K−π+ decay mode for calibration, the lifetime ratio and the absolute lifetime of the Ω−b baryon are measured to be τΩ−b/τΞ−b=1.11±0.16±0.03, τΩ−b=1.78±0.26±0.05±0.06 ps, where the uncertainties are statistical, systematic and from the calibration mode (for τΩ−b only). A measurement is also made of the mass difference, mΩ−b−mΞ−b, and the corresponding Ω−b mass, which yields mΩ−b−mΞ−b=247.4±3.2±0.5 MeV/c2, mΩ−b=6045.1±3.2±0.5±0.6 MeV/c2. These results are consistent with previous measurements.
*LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 702 weitere Personen]
Im Titel ist [Omega] als griechischer Buchstabe dargestellt
Im Titel ist das Zeichen - hochgestellt
Im Titel ist der Buchstabe b tiefgestellt
Gesehen am 14.07.2020